Problematika Komunikasi Politik Pendanaan Pembangunan Ibu Kota Negara Nusantara - Abdul Rahman Ma'mun (Universitas Warmadewa, 2023)
This paper discusses the issue of the policy of relocating the National Capital (IKN) which has raised controversy, lawsuits and rejection from some people, even though it has been supported by the IKN Law Number 3 of 2022. The purpose of writing this article is to answer the question of how to communicate the political communication of the policy of relocating the IKN and why do political communication problems arise regarding funding for the development of the IKN Nusantara? Political communication theory from Pureklolon (2016) and Harold D. Laswell (2016) is used to analyze political communication from actors, the Government, to the media and the public with 'messages' regarding IKN funding. Political economy theory a classical approach from Caporaso (2008) is used to analyze the choice of IKN funding policies that rely on the private sector and foreign investors rather than the state budget. This study uses a qualitative method with inductive and descriptive analytical data analysis, namely building patterns, categories, and themes from the bottom up (inductive), from empirical observations of socio-political phenomena. The results of the discussion of this study show that the problems of political communication in IKN funding arise due to 3 factors, (1) There is no political communication strategy plan for relocating the IKN in the Strategic Plan of the Ministry of Communication and Informatics (Kemkominfo) 2020-2024 even though IKN is a national strategic program. It is not clear who the Government's 'communicator' is and there is no 'single narrative' as the main 'message' of political communication (2) Transparency of IKN funding sources and when funding from investors does not meet expectations is also unclear (3) Crisis communication mitigation is not prepared to overcome political communication with potential investors or the public. The three factors causing the problem of political communication on IKN funding, if left unchecked, will make the public tend to doubt that the issue of IKN funding will be able to be managed properly by the Government.